1868 Ark. Acts 218, Acts of the General Assembly of Arkansas, § 13 - (:unkn) unknown (General Publisher, 1868)
Any person who draws a pistol, gun, or any other deadly weapon on any other person or citizen for the purpose of frightening or intimidation from lawful acts when not justified in self-defense. Violators guilty of a high misdemeanor, fined not less than five hundred nor more than one thousand dollars, and imprisoned for twelve months.
--
Keywords: BRANDISHING